Mosque-Based Integrated Community Empowerment Model - bin Mislan Cokrohadisumarto, Widiyanto; Sari, Yuli Indah (Islamic Social Finance, 2024)
This study aims to develop Indonesia's mosque-based integrated community empowerment model.  The model collaboration defined the mosque as a place of productive empowerment to overcome poverty in Indonesia. This study used a qualitative approach that began with a literature study to get research direction and then continued with FGD activities with (1) takmir or administrator of the mosque from the Indonesian Mosque Council or Dewan Masjid Indonesia (DMI), (2) managers of the Amil Zakat Infaq and Sadaqah Insititute or Lembaga Amal, Zakat, Infaq, dan Sedekah (LAZIS), (3) religious leaders or ulama, and (4) academician (who have expertise in Islamic economics and finance, management, and information technology). Based on the study, a model that optimally empowers mosque-based communities (to help solve poverty problems in society around the mosque), it is necessary to have integrated the mosque involvement from many parties such as government, DMI, Aghniya, LAZIS, religious leaders, universities, and mosque. This research makes a valuable contribution by employing a holistic and integrated approach to address poverty-related issues while simultaneously strengthening the role of mosques as productive empowerment centres. It combines elements of Islamic economics, management, and information technology.